Characterization of glycosyl dioxolenium ions and their role in glycosylation reactions - Thomas Hansen (Nature Portfolio, 2020)
Dioxolenium ion intermediates formed from remote positions are hypothesized to direct stereoselective glycosylations. Herein we combine infrared ion spectroscopy, DFT calculations and synthetic work to characterize and study these dioxolenium ions and their role in stereoselective glycosylation reactions.